Variasi Molaritas Naoh Pada Stabilisasi Geopolimer Abu Terbang Dengan Tambahan Portland Composite Cement - Oktariyansa, Randy; Wibisono, Gunawan; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Land as a supporting media for the establishment of structures is an important part to consider. Peat soils have a very low carrying capacity, very high compressibility and others that are not favourable for construction. This study aims to examine the strength of stabilized peat soils using fly ash geopolymers with the addition of PCC cement (Portland Composite Cement). Soil stabilization using geopolymer added ingredients as an alternative in soil improvement in construction. Cement was used from a variation of 20%, 25%, and 30% by weight of the total binder used. The alkaline activator solution used consists of a solution of Sodium Hydroxide (NaOH) and a solution of sodium silicate (Na2SiO3), NaOH concentrations used were 10 M, 12 M, and 14 M. Stabilization of peat soils with 7, 28, and 56 days treatment. It is obtained that at the age of 56 days, the compressive strength value of peat soil is 152,3 kPa, 162,55 kPa, 142,02 kPa, respectively at the NaOH concentration of 10M, 12M, 14M. The NaOH molarity influences the compressive strength of the soil stabilized with the geopolymer. The lower the water water content of the test material, the higher the compressive strength of the soil. Keywords : Stabilization, peat soils, geopolymers, fly ash, Portland Composite Cement